Climate change resilient development of family farmers in the brazilian semiarid : an analysis of public policies and of the coexisting with the semiarid paradigm - Letícia Wittlin, Machado (2018)
The Brazilian Semiarid region comprises the poorest people in the country, and one of the two biomes most vulnerable to climate change in Brazil. Public policies have been focused on droughts, but a more organized and articulated civil society in the 1980´s started to seek alternatives to addressing the complex challenges in the region, focusing on more holistic solutions for human coexistence with the Semiarid conditions. This thesis analyses public policies during three historical periods and the civil society-led paradigm Convivência com o Semiárido (CSA, Coexisting with the Semiarid) to verify if they promoted resilience to climate change for family farmers. The research follows a theoretical framework of Social-Ecological Systems and Resilience Thinking, and uses document analysis, fieldwork and interviews. It was found that recent public policies have assisted family farmers to improve living conditions and face droughts impacts, but they have not substantially promoted climate change resilience. Therefore, achievements gained through public policies are at risk, as the changes in climate create new environmental and economic conditions. Concurrently, CSA increases family farmers` climate resilience by applying social technologies through a participatory approach, building local knowledge and promoting the sustainable use of resources. In accordance to resilience theory, CSA is a social process with the potential to drive transformational change, which can be sustained into the future. It only succeeds, however, when several activities are combined. It focuses on civil society rather than the government sphere as pivotal agent of transformation.